2011
DOI: 10.3168/jds.2010-4002
|View full text |Cite
|
Sign up to set email alerts
|

Automatic recording of daily walkover liveweight of dairy cattle at pasture in the first 100 days in milk

Abstract: Daily walkover liveweight (WoLW) records (n=79,697) from 463 pasture-fed dairy cows from a single dairy herd in the lower North Island of New Zealand were recorded over the first 100 d of lactation. The aims of this study were to (1) describe LW records retrieved by a standalone automatic Wo daily weighing system; (2) describe the frequency and nature of outlier LW records measured by the system and develop an approach for excluding identified outlier LW records; (3) quantify the agreement between cow LW measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 26 publications
7
37
0
1
Order By: Relevance
“…A different approach is to instrument the floor of the robot to detect weight. Alawneh et al (2011) showed that daily variability (SD 17 kg) of weight could be overcome by taking an 8 day rolling mean. The standard deviation of daily live weight (LW) measurements across parities was 17 kg, on average.…”
mentioning
confidence: 99%
“…A different approach is to instrument the floor of the robot to detect weight. Alawneh et al (2011) showed that daily variability (SD 17 kg) of weight could be overcome by taking an 8 day rolling mean. The standard deviation of daily live weight (LW) measurements across parities was 17 kg, on average.…”
mentioning
confidence: 99%
“…Comparing the relative frequency of classified 'physiologically extreme' and 'implausible' milk performances with 1.2% of all observations to the findings of Wiggans et al [5], who identified 1.9% abnormal test day milk records, the same order of magnitude for conspicuous observations can be identified. In other automatic measurements, such as walkover live weight recording, Alawneh et al [9] found a much higher frequency of conspicuous observations. The authors detected a total of 12% outliers, of which they classified 25% as 'biologically implausible' and 75% as 'potentially erroneous'.…”
Section: Classification Of Observations and Descriptive Statisticsmentioning
confidence: 96%
“…However, there are also approaches to further discriminate the source of extreme observations. Alawneh et al [9] for example investigated the daily walkover live weight of cows and differentiated identified outliers into 'biologically implausible' or 'potentially erroneous'. The authors made these classifications based on a smoothed live weight curve, where observations outside the ±4 standard deviation (SD) interval were classified as 'biologically implausible' and observations outside the ±1.96 SD interval (95% confidence interval) as 'potentially erroneous' cases.…”
Section: Introductionmentioning
confidence: 99%
“…They compared the dynamic weights with actual static weights, which confirmed the feasibility and effectiveness of the dynamic weighing method in the evaluation of cow weights. Alawneh et al [ 19 ] recorded the daily live weight variations in 463 cows at a dairy farm in northern New Zealand, and the standard deviation of the measured value was 17 kg; they obtained the live weights of cows through autocorrelation analysis, and these weights were used to adjust the cattle feeding plan and detect changes in the bodies of cows. E. Gonzalez-Garcia et al [ 20 ] designed a mobile automatic weighing system based on an environment with outdoor free-range sheep and encouraged the voluntary weighing of sheep combined with stimulations of water and mineral salt intake; this approach not only saved human and material resources but also improved animal productivity and welfare.…”
Section: Introductionmentioning
confidence: 99%